Motivation in the learning of mathematics - Md. Yunus, Aida Suraya; Wan Ali, Wan Zah (European Journal of Social Sciences, 2009)
This study focuses on students’ motivation in solving mathematical problems. Objectives of the study are to (i) identify students’ level of effort, self efficacy and worry in solving mathematical problems based on gender, current cumulative grade point average (CGPA)and year of study; (ii) students’ level of motivation in solving mathematical problems based on gender, current cumulative grade point average (CGPA) and year of study; and (iii)establish relationship between levels of motivation and students’ mathematics achievement. The subscales used in the measurement of motivation are effort, self-efficacy, and worry. Data was gathered through a descriptive survey using questionnaires. Overall, students’ motivations was found to be high and majority of the respondents were in the high level for effort but were only moderate for self efficacy. Significant difference was established in overall motivation scores between the female and male respondents, but not for the subscales effort, self-efficacy and worry. Respondents with higher CGPA obtained higher overall scores for motivation. Significant positive correlations were established between effort, self-efficacy, and overall motivation with students’ overall academic achievement. Likewise, significant positive correlations were established between effort, self-efficacy, worry, and overall motivation with students’ average mathematics achievement.